Fuente Langas, Jesús Mª y Víctor Manuel Arbeloa Muru, El socialismo en Pamplona y Navarra, 1931-1936, Pamplona, Eunsa, 2021, 770p. ISBN: 9788431336707. 37,90€ (Memoria y Civilización, 2022)
Book Review